Anticorpos IgG e IgM Anti-α-GAL (Galα1,3Galβ1,4GlcNAc-R) em pacientes infectados por Plasmodium vivax - Zélia Barbosa de Almeida Coelho (2018)
Plasmodium vivax is the most widely distributed plasmodium species in the world. In Brazil it is the main species associated with malaria infection. The recognition of occurrence of severe malaria cases in P. vivax infections has directed different studies to determine the mechanisms associated with morbidity and susceptibility to this parasite. Autoantibodies have been considered important components of the immune response and their potential to determine immunological mechanisms of destruction by infected and uninfected cells during malaria has been considered by our group. About 1% to 5% of circulating IgG e IgM antibodies repertoire are targeted to α-Gal epitope in healthy individuals and such antibodies are naturally produced in response to antigenic stimulation by bacteria of the gastrointestinal tract. Studies have shown that production of anti-α-Gal antibodies in some parasitic diseases is associated with presence of α-Gal epitope in the parasite. Antigens with α-Gal domains have already been identified in asexual blood stages of P. falciparum and anti-α-Gal antibody production has been associated with protection against malaria. Thus, the present study aims to determine the response profile of anti-α-Gal IgG and IgM antibodies during P. vivax malaria. For this purpose, P. vivax infected patients had their anti-α-Gal IgG and IgM antibodies levels measured and correlated to epidemiological (age), parasitological (parasite levels detected using thick blood smears, previous exposure to malaria), clinical (presence of anaemia and thrombocytopenia) and haematological variables (ABO blood group system). P. vivax infected individuals showed elevated levels of anti-α-Gal IgG and IgM antibodies, indicating that such immunoglobulins could play an important role in malaria vivax. No association was observed between anti-α-Gal antibody levels and blood groups of ABO system. A positive association was found between anti-α-Gal IgG and parasitemia in patients with vivax malaria. However, such antibodies did not stimulate phagocytosis of uninfected erythrocytes in vitro, independent of blood group. Such results may contribute to a better understanding of the host immune response during vivax malaria and, in long term, it may allow the development of disease control strategies in endemic countries.